Sosialisasi Penyusunan Laporan Keuangan UMKM - Eldi Eldi; Syamsul Alam; Nur Syamsu; Bungatang Bungatang; Chaerunnisa Rumianti; Yana Fajriah; Muhammad Tafsir (Universitas Maritim AMNI Semarang, 2024)
The socialization activity for preparing financial reports among MSME players aims to provide understanding and increase knowledge of methods for preparing financial reports. This activity was carried out in Sanrobone village, Takalar district, South Sulawesi. This socialization activity was carried out in collaboration with STIEM Bongaya Makassar with the Sanrobone village government, Takalar and was attended by 15 business actors. The method of implementing activities is carried out by conducting short training and assistance in preparing financial reports in particular. Based on the results of the activities that have been described, the conclusion from the community service activities is that the development of MSMEs has gone well and the existence of MSMEs has provided many benefits to the local community. There are several obstacles in managing the business, namely the ability of actors is still low, the market share of goods/services is low. UMKM production is still limited, there is a lack of capital, they do not have a good bookkeeping system. Training activities provide benefits in increasing the ability and ease in managing UMKM finances. Follow-up activities are expected to be more technical in the form of training and technical guidance related to the preparation of UMKM financial reports, both in terms of manual or application-based.